2021
DOI: 10.3390/microorganisms9030505
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference-Mediated Knockdown of Genes Encoding Spore Wall Proteins Confers Protection against Nosema ceranae Infection in the European Honey Bee, Apis mellifera

Abstract: Nosema ceranae (Opisthosporidia: Microsporidia) is an emergent intracellular parasite of the European honey bee (Apis mellifera) and causes serious Nosema disease which has been associated with worldwide honey bee colony losses. The only registered treatment for Nosema disease is fumagillin-b, and this has raised concerns about resistance and off-target effects. Fumagillin-B is banned from use in honey bee colonies in many countries, particularly in Europe. As a result, there is an urgent need for new and effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 89 publications
1
6
0
Order By: Relevance
“…Porphyrins have been documented to act directly on N. ceranae microsporidia; however, their potential effects on honeybee immunity have yet to be explored. Before analyzing the impact of porphyrins on the immune system in both the non-infected and Nosema- infected honeybees, we verified that the parasite proliferated in the host and significantly reduced its lifespan, as observed in previous studies 1 , 3 , 37 , 46 , 47 . The present work confirmed the negative impact of N. ceranae on the bee lifespan.…”
Section: Discussionsupporting
confidence: 76%
“…Porphyrins have been documented to act directly on N. ceranae microsporidia; however, their potential effects on honeybee immunity have yet to be explored. Before analyzing the impact of porphyrins on the immune system in both the non-infected and Nosema- infected honeybees, we verified that the parasite proliferated in the host and significantly reduced its lifespan, as observed in previous studies 1 , 3 , 37 , 46 , 47 . The present work confirmed the negative impact of N. ceranae on the bee lifespan.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, efforts to find new treatment strategies are critical to protect honey bees from this parasite [ 16 , 19 ]. Many promising alternatives strategies for control of N. ceranae infection have now been pursued, including important studies exploring other small molecules, RNAi, probiotics, and various natural compounds ([ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] and work prior to 2020 reviewed in [ 30 ]). Eukaryotic pathogens can be challenging to combat using chemical antimicrobials because of the phylogenetic closeness with their hosts, and microsporidia are no exception.…”
Section: Introductionmentioning
confidence: 99%
“…RNA interference (RNAi) is currently being explored for pesticide activity in agriculture and as a potent and specific strategy for controlling infections of parasites and pathogens in insects, including honey bees [ 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ]. Several studies evidence that RNAi might be exploited to regulate Nosema gene expression within bee hosts [ 139 , 140 , 141 ].…”
Section: Rna Interferencementioning
confidence: 99%
“…Another recent study used RNAi to lower the expression of polar tube protein 3 (ptp3), a protein essential for sporoplasm injection and microsporidian cellular invasion [ 145 ]. He et al [ 141 ] explored the therapeutic potential of silencing the sequences of two N. ceranae encoded spore wall protein (SWP) genes employing the RNAi-based methodology. This study revealed that the oral ingestion of dsRNAs corresponding to SWP8 and SWP12 , used separately or in combination, could lead to a significant reduction in spore load, improved immunity and extended lifespan of N. ceranae infected bees.…”
Section: Rna Interferencementioning
confidence: 99%